Characterization of Diamond and Silicon Carbide Detectors With Fission Fragments - Gallin-Martel, M. L.; Kim, Y. H.; Abbassi, L.; Bes, A.; Boiano, C.; Brambilla, S.; Collot, J.; Colombi, G.; Crozes, T.; Curtoni, S.; Dauvergne, D.; Destouches, C.; et al. (Frontiers in Physics, 2021)
Experimental fission studies for reaction physics or nuclear spectroscopy respectively can profit from fast, efficient, and radiation-resistant fission fragment (FF) detectors. When such experiments are performed in-beam in intense thermal neutron beams, additional constraints arise in terms of target-detector interface, beam-induced background, etc. Therefore, wide gap semi-conductor detectors were tested with the aim of developing innovative instrumentation for such applications. The detector characterization was performed with mass- and energy-separated fission fragment beams at the ILL-LOHENGRIN spectrometer. Two single crystal diamonds, three polycrystalline and one diamond-on-iridium as well as a silicon carbide detector were characterized as solid state ionization chamber for FF detection. Timing measurements were performed with a 500-µm thick single crystal diamond detector read out by a broadband amplifier. A timing resolution of ~10.2 ps RMS was obtained for FF with mass A=98 at 90 MeV kinetic energy. Using a spectroscopic preamplifier developed at INFN-Milano, the energy resolution measured for the same FF was found to be slightly better for a ~50-µm thin single crystal diamond detector (~1.4% RMS) than for the 500-µm thick one (~1.6% RMS), while a value of 3.4 % RMS was obtained with the 400-µm silicon carbide detector. The Pulse Height Defect (PHD), which is significant in silicon detectors, was also investigated with the two single crystal diamond detectors. The comparison with results from α and triton measurements enabled us to conclude that PHD leads to ~50% loss of the initial generated charge carriers for FF. In view of these results, a possible detector configuration and integration for in-beam experiments has been discussed.